Oh! Poor me, llorona! Yesterday I was a wonder, oh! and now I’m not even a shadow. La llorona as part of the collective memory and social imaginary in the son jarocho [from Veracruz] - Hernández Cázares, María Arcelia (Huarte de San Juan. Geografía e Historia, 2023)
The son jarocho is a musical practice that is currently performed in the south of Veracruz and in some towns in Oaxaca and Tabasco, Mexico. It is made up of string instruments, percussion, stage dance and singing, which as a whole allows us to glimpse the syncretism of its Indigenous, African and Hispanic origins. The repertoire of the son jarocho is wide and its content narrates from everyday events to fantasy situations, allowing us to access through listening to part of the collective memory andsocial imaginaries that are reflected on the lyrics. Therefore, the objective of this article is to show how the character of La Llorona is still inserted in part of the collective memory and how the constructions of the social imaginary haveallowed her to adapt to different sociohistorical contexts, ensuring her survival until the 21st century.
Keywords: Son jarocho; Collective memory; Social imaginary; Llorona; Lyrics